Analysis of Energy Transformation Through Biofuel Energy Downstream to The National Economy - Ica Cahayani; Elyana Ade Pertiwi; Arina Nihayati (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
This research discusses energy transformation through downstream biofuel energy to the national economy in terms of how biofuels reduce the use of fossil energy and encourage national economic growth. Biofuel energy transformation is proposed because of its increasing popularity amid increasingly high climate change and world oil prices have increased due to world political uncertainty. The choice of biofuel energy transformation is the right way to find out how significant the energy transformation from fossil energy to biofuel energy has impact on energy availability and the national economy. This study analyzes Indonesia's energy transformation through downstream biofuel energy using the concept of energy transformation in looking at the integration of biofuel energy into the national economy. This study uses an integrative review method of presenting non-experimental data, a systematic approach, and uses a detailed search strategy in an effort to identify relevant evidence for biofuel energy and its impact on the Indonesian national economy. The energy transformation policy through downstream biofuel energy has not had a positive impact on Indonesia's national economy even though biofuel energy is cheap and environmentally friendly. The energy needs of the Indonesian people are very large and have not been able to be supported by biofuel energy with the same raw materials as the people's staple food. Meanwhile, food waste, such as tofu production waste and sugar production waste, is only able to sustain the energy needs of small-scale communities. The reallocation of fossil energy subsidies to biofuel energy has not yet contributed to the national economy.Â